Moderators of the intention-behaviour and perceived behavioural control-behaviour relationships for leisure-time physical activity - Godin Gaston; Amireault Steve; Vohl Marie-Claude; Pérusse Louis (BMC, 2008)
Abstract Background Intention is a key determinant of action. However, there is a gap between intention and behavioural performance that remains to be explained. Therefore, the aim of this study was to identify moderators of the intention-behaviour and perceived behavioural control (PBC)- behaviour relationships for leisure-time physical activity. Method This was tested in reference to Ajzen's Theory of Planned Behaviour. A sample of 300 volunteers, 192 women and 108 men, aged 18 to 55, participated in the study. At baseline, the participants completed a self-administrated psychosocial questionnaire assessing Ajzen's theory variables (i.e., intention and perceived behavioural control). The behavioural measure was obtained by mail three months later. Results Multiple hierarchical regression analyses indicated that age and annual income moderated the intention-behaviour and PBC-behaviour relationships. However, in the final model predicting behaviour (R2 = .46), only the interaction term of PBC by annual income (β = .24, p = 0.0003) significantly contributed to the prediction of behaviour along with intention (β = .49, p = 0.0009) and past behaviour (β = .44, p < 0.0001). Conclusion Physical activity promotion programs would benefit not only from focusing on increasing the intention of low intenders, but also from targeting factors that moderate the perceived behavioural control-behaviour relationships.